1993
DOI: 10.1139/b93-197
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of dominant species of arbuscular mycorrhizae in burned and unburned sand prairies

Abstract: Seasonal variation in abundance of spores of arbuscular mycorrhizal fungi was examined for four growing seasons on burned and unburned sand prairies in Illinois. The three leading mycorrhizal species were an undescribed species of Glomus, Scutettospora heterogama, and Sclerocystis rubiformis, in order of decreasing abundance. Mycorrhizal spore abundance for all species generally showed similar seasonal patterns on burned and unburned sites during the sampling period, i.e., minimal in the middle of the growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…Spore density showed variation, maximum in premonsoon and minimum in the monsoon season at both sites. Similar observations have been reported in earlier studies [29,30]. Higher spore density in premonsoon season is thought to be an indication of root senescence and available nutrients, stimulating fungal sporulation as plant nutrient requirement is reduced [31].…”
Section: Discussionsupporting
confidence: 88%
“…Spore density showed variation, maximum in premonsoon and minimum in the monsoon season at both sites. Similar observations have been reported in earlier studies [29,30]. Higher spore density in premonsoon season is thought to be an indication of root senescence and available nutrients, stimulating fungal sporulation as plant nutrient requirement is reduced [31].…”
Section: Discussionsupporting
confidence: 88%
“…Fire can alter AM fungal species distributions depending on the timing, extent, and intensity of the burn (Bentivenga and Hetrick 1991;Eom et al 1999;Dhillion and Anderson 1993). Forces that initiate primary succession, such as glacial retreat and volcanic flow, create substantial soil disturbance and also influence AM fungal distributions.…”
Section: Disturbance Historymentioning
confidence: 99%
“…Douds and Millner (1999) found that the study of AMF diversity in agricultural soils presents many challenges, including the difficulty in identifying field collected spores, the detection of non-sporulating members of the community, and the lack of correlation between functional and morphological features of the spores used to define the different species. Dhillion and Anderson (1993) showed that in sand prairies the abundance of spores was always significantly lower in burned than in unburned sites early in the growing season. Ortas et al (2000) reported that soil and crop management can help to get maximum benefit from indigenous mycorrhiza for sustainable crop production.…”
Section: Introductionmentioning
confidence: 97%